The Lion and the Star : Gentile-Jewish Relations in Three Hessian Towns, 1919-1945 - Friedman, Jonathan C., 1966- (Book collections on Project MUSE., 1998)
The Lion and the Star not only offers an informed glimpse into the intricacies of daily German life but also confirms the continuing danger of making sweeping generalizations about German Jews and non-Jews. In the aftermath of World War II, many viewed the Third Reich as an aberration in German history and laid blame with Hitler and his followers. Since the 1960s, historians have widened their focus, implicating ""ordinary"" Germans in the demise of German Jewry.Jonathan Friedman addresses this issue by investigation everyday relations between German Jews and their Gentile neighbors. Friedman.